'Flying Gas Mains': Rumour, Secrecy, and Morale during the V-2 Bombardment of Britain. (27th September 2021) - Hall, Charlie
Abstract: Britain was the first country to suffer casualties as the result of a ballistic missile attack, when German V-2 rockets began landing in London and the South-East in September 1944. This new menace posed critical challenges, not only to the civilians whose lives were endangered once again, but also to the British government. Policymakers had to decide what, if any, information they released to the public, amid fears of creating panic, providing free propaganda to the Nazis, and helping the V-2 launching units improve their aim. Their commitment to secrecy in this period was both resolute and largely unnecessary, not to mention ineffective. In the absence of official information released from above, the public drew their own conclusions and myriad rumours emerged, many of which were remarkably accurate. This article will explore the ways in which government policy surrounding censorship and publicity changed during the V-2 bombardment and the extent to which this affected those in the firing line. It will also add considerable nuance to our understanding of public morale in this period, which was rather less steadfast than many accounts suggest, and which continued to be a major government preoccupation, despite the diminishing likelihood of a descent into mass panic or defeatism.